Tuna Fish Commodity Balance In Indonesia - Ciptaningtyas, Intan Savitri; Hidayat, Syarif Imam; Fitriana, Nisa Hafi Idhoh (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2025)
Commodity balance is a collection of data and information that describes the consumption and production conditions of a particular commodity, both to meet the needs of the community and the industrial sector in a certain period of time and applies nationally. Analysis of the tuna commodity balance in Indonesia is very important to understand the balance between production and consumption and its impact on fisheries policy and the national economy. In addition, forecasting tuna production and consumption also plays a crucial role in ensuring resource sustainability and market balance in the future. However, issues such as overfishing, infrastructure limitations, and low domestic consumption pose significant challenges that need to be addressed. Therefore, the objectives of this study are: (1) analyze the tuna commodity balance in Indonesia, and (2) forecast tuna production and consumption in Indonesia. This research takes the object of Indonesia to Japan. The data used is quantitative with secondary data sources from Badan Pusat Statistik (BPS) and Kementerian Kelautan dan Perikanan (KKP) from 1994 - 2023. Time series data for 30 years were analyzed using quantitative methods with a descriptive approach for commodity balance analysis and ARIMA models for forecasting tuna production and consumption in Indonesia, selected based on stationarity tests, ACF-PACF plots, and the lowest AIC, SC, and HC criteria. The ARIMA (1, 1, 0) model was selected as the best model for production, while ARIMA (0, 1, 1) was chosen for consumption. Forecasting using ARIMA indicates an upward trend in both tuna production and consumption from 2024 to 2030. Policy recommendations for the government to improve production efficiency, strengthen product quality according to export standards, and expand domestic market access to increase national tuna consumption.